Comorbidities at diagnosis of rheumatoid arthritis: a population-based case-control study. (17th December 2020) - Tidblad, Liselotte; Westerlind, Helga; Delcoigne, Bénédicte; Askling, Johan; Saevarsdottir, Saedis
Abstract: Objectives: Comorbidities contribute to the morbidity and mortality in RA, and are thus important to capture and treat early. In contrast to the well-studied comorbidity risks in established RA, less is known about the comorbidity pattern up until diagnosis of RA. We therefore compared whether the occurrence of defined conditions, and the overall comorbidity burden at RA diagnosis, is different from that in the general population, and if it differs between seropositive and seronegative RA. Methods: Using Swedish national clinical and demographic registers, we identified new-onset RA patients ( n = 11 086), and matched (1:5) to general population controls ( n = 54 813). Comorbidities prior to RA diagnosis were identified in the Patient and Prescribed Drug Registers, and compared using logistic regression. Results: At diagnosis of RA, respiratory (odds ratio (OR) = 1.58, 95% CI: 1.44, 1.74), endocrine (OR = 1.39, 95% CI: 1.31, 1.47) and certain neurological diseases (OR = 1.73, 95% CI: 1.59, 1.89) were more common in RA vs controls, with a similar pattern in seropositive and seronegative RA. In contrast, psychiatric disorders (OR = 0.87, 95% CI: 0.82, 0.92) and malignancies (OR = 0.88, 95% CI: 0.79, 0.97) were less commonly diagnosed in RA vs controls. The comorbidity burden was slightly higher in RA patients compared with controls ( P <0.0001). Conclusion: We found several differences in comorbidity prevalence between patients with new-onset seropositive and seronegative RA compared with matched controls from the general population. These findings are important both for our understanding of the evolvement of comorbidities in established RA and for early detection of these conditions.